Regional differences of nontuberculous mycobacteria species in Ulsan, Korea - Lee, Mu Yeol (Pioneer Bioscience Publishing Company, 2014)
BACKGROUND: In Korea recently, nontuberculous mycobacteria (NTM) have been more frequently isolated in respiratory specimens, while Mycobacterium tuberculosis (MTB) isolations have decreased. The major NTM lung disease species in Korea are M. intracellulare, M. avium, and M. abscessus, whereas M. kansasii is a rare species. This retrospective study was performed to determine if there are region-specific characteristics of lung disease-causing NTM species in Ulsan, a highly industrialized city in Korea. METHODS: Between January 2010 and July 2013, the results of all acid-fast bacilli (AFB) cultures of respiratory specimens performed at Ulsan University Hospital (Ulsan, Korea) were collected. NTM were identified and regional differences of NTM species were compared. RESULTS: AFB cultures were performed on 33,567 respiratory specimens, obtained from 10,208 patients, during the study period. Further, 10% of the specimens (3,287/33,567) were AFB culture-positive [MTB, 2,288/3,287 (70%); NTM 999/3,287 (30%)]. The proportion of NTM isolations gradually increased between 2010 and 2013, at 25% and 38%, respectively. The most common NTM species was M. intracellulare (356/999, 36%), followed by M. kansasii (295/999, 30%), M. avium (161/999, 16%), M. abscessus (117/999, 12%) and M. fortuitum (39/999, 4%). This trend was maintained throughout the study period. CONCLUSIONS: In Ulsan, NTM isolation from respiratory specimens is increasing, consistent with previous studies performed in Korea. The distribution of respiratory NTM species, however, differed from previous studies that were performed in other regions of Korea: M. kansasii was the second most common NTM species in Ulsan. In Ulsan, there is a regional difference in the NTM species isolated.